Behavior of the LSAW loss in multi‐layer systems - Wallner, Paul; Ruile, Werner; Weigel, Robert (137th Meeting of the Acoustical Society of America (ASA), 1999)
Compared with common SAW, the leaky SAW shows attenuation even if material‐dependent loss types like viscosity, dielectric damping, or airloading are neglected. In fact, this typically LSAW loss is caused by a pure bulk wave emission into the piezoelectric substrate. For the search of low‐loss crystal cuts it is important that this kind of loss strongly depends on the crystal cut. Only such crystal cuts are important for technical use where this leaky loss shows a minimum. Moreover, former investigations confirmed that an additional metal layer on the piezoelectric substrate can shift the minimum loss to other crystal cut angles, e.g., the shift from 36rotYX to 42rotYX LiTaO3 with 10% Al. New computations show that this behavior can be understood as a general effect: The shift depends on the material constants of layer and substrate. In multi‐layer structures all the material constants influence the angle of minimum propagation loss. A distinct angle of minimum can be reached by using a distinct ratio of the layers. This means, if the ratio differs from 10% Al or the aluminum layer is covered with a second layer, the minimum of propagation loss due to bulk wave emission is shifted away from 42rotYX LiTaO3
elib2cris::1512001600,wallner1999